A RESPONSE To Everett L. Wheeler’s Review of “The Armenian Military in the Byzantine Empire: Conflict and Alliance under Justinian and Maurice” (Alfortville: Sigest, 2012) - Ayvazyan, Armen (Armenian Folia Anglistika, 2013)
The present article-response denies the groundless statements in Everett L. Wheeler’s review of A. Ayvazyan’s monograph titled The Armenian Military in the Byzantine Empire: Conflict and Alliance under Justinian and Maurice (Alfortville: Sigest, 2012). Furthermore, the author has identified the amateurism, historical-factual and theoretical mistakes, bias and anti-Armenian motives of the writer in the article. The shortened version of the present article has been published in the Journal of Military History, July 2013 issue (vol. 77, no. 3), pp.1207-1210).